Response Surface Optimization of Crude Polysaccharides from Grey Oyster Mushroom (Pleurotus sajor-caju (Fr.) Singer) Using Pressurized Hot Water Extraction - Winatta Sakdasri; Panisara Arnutpongchai; Supasuta Phonsavat; Ruengwit Sawangkeaw (My University, 2021)
Grey oyster mushroom (Pleurotus sajor-caju (Fr.) Singer) is a popular edible mushroom in Thailand due to its high nutritional and medicinal benefits. This study aims to study the effects of temperature (100–140 °C), pressure (4–7 bar), and extraction time (20–60 min) on the extraction of crude polysaccharides with environmentally friendly pressurized hot water. The extraction conditions were optimized by the maximize yield using response surface method based on a central composite design (CCD). The temperature was the main factor affecting the increase in the extracted yield. The optimum extraction conditions were 140 °C, 10 bar, and 26.79 min, with a corresponding yield of 31.31 ± 2.55%. Under these conditions, the total phenolic content of crude polysaccharides was 401 ± 8.24 mg GAE/g dry mushroom. In addition, the total glucan content was indicated as 34.50 ± 1.79 g/100 g dry mushroom, which was separated as 32.47 ± 1.95 mg/100 g of β-glucans and 2.04 ± 0.98 mg/100 g of α-glucans.
Keywords: Pleurotus; Hot water extraction; Dry weight; Fungal Biology and Applications